THE ASSOCIATION BETWEEN PERCEIVED STRESS AND EATING PATTERNS AMONG UNIVERSITY STUDENTS - Jovanovska, Slavica Gjorgievska; Manchevska, Sanja (Journal of Morphological Sciences, 2025)
Background: Psychological stress is known to significantly influence health associated behaviors, especially in student population. The challenges of academic life and the transition to adulthood often contribute to the development of poor dietary habits during university years. Objective: This study aimed to examine the association between the levels of perceived stress and eating behaviors in university students. Methods: A cross-sectional survey was conducted among 200 students enrolled at the Law Faculty and the High Medical School of the University “St. Kliment Ohridski” – Bitola. Data were collected using three tools: a demographic questionnaire, the Perceived Stress Scale (PSS-10), and the Weight-Related Eating Questionnaire (WREQ). Statistical analyses included chi-square tests, correlation assessments, and ANOVA. Results: The majority of participants reported moderate levels of stress, with female students exhibiting significantly higher stress scores (p = 0.0125). A positive correlation was observed between stress levels and disordered eating patterns, particularly emotional eating (p = 0.0082). Conclusion: The findings indicate that emotional eating is a prevalent coping mechanism among distressed university students, with a stronger expression observed in males. Student-centered support programs that focus on stress reduction and healthy nutrition should be implemented as essential tools for promoting university student health and well-being. Keywords: Perceived stress, emotional eating, university students.